Behavior of Steel-Fiber Reinforced Lightweight Self-Compacting Concrete Containing LECA after the Exposure to Internal Sulfate Attack - Motar Shahad B.; Awad Hadeel K. (E3S Web of Conferences, 2023)
For many years, lightweight concretes (LWC) have been utilized successfully in the construction of buildings because of their low specific weight, high thermal insulation capacity, and sound insulation. The development that led to lightweight self-compacting concrete (LWSCC) is a significant step forward in recent years. These concrete chains self-compacting concrete's beneficial properties with lightweight concrete. The purpose of this experimental investigation is to determine how the internal sulfates attack effect fresh and hard properties of lightweight self-compacting concrete (LWSCC) made by using lightweight expanded clay aggregate (LECA) before and after the addition of 0.5 volume fraction (Vf) of steel fibers. In fine aggregate, several concrete mixes were cast in different SO3 percentages (0.34, 2, 4, and 6%). The fresh properties of LWSCC concrete were tested, such as (slump, sieve segregation resistance, and L-box test). The hard properties of LWSCC were (Compressive, splitting tensile strength, flexural strength, oven-dried density, and modules of elasticity). The results showed that the presence of SO3 in fine aggregate affects the properties of LWSCC. A significant decrease in fresh properties of LWSCC mixes with (2, 4, and 6%) of SO3 in fine aggregate. In addition, the mechanical properties (compressive St., splitting tensile St., flexural St., density, and modulus of elasticity) decreased as curing age increased, and SO3% increased. When sulfate percent rose from (0.34% to 2%, 4%, and 6%) in compressive St., the reduction was (16.53, 22.45, and 26.47%) at 120 days. Adding 0.5% Vf of steel fiber enhanced the mechanical properties of LWSCC.